2014
DOI: 10.1016/j.alcr.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Residential context, migration and fertility in a modern urban society

Abstract: This study examines fertility variation by residential context in Britain. While there is a large literature on fertility trends and determinants in industrialised countries, to date longitudinal research on spatial fertility variation has been restricted to the Nordic countries. We study fertility variation across regions of different sizes, and within urban regions by distinguishing between central cities and suburbs. We use vital statistics and longitudinal data and apply event history analysis. We investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0
8

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 25 publications
1
93
0
8
Order By: Relevance
“…Additionally, the fact that employment status was available only for a subsample should not challenge the results of the study. The effect of employment status on fertility is consistent with that observed in other studies (e.g., Kulu and Washbrook 2014). Does this finding suggest that cultural factors explain the high fertility among women of Pakistani and Bangladeshi descent in the UK?…”
Section: Summary and Discussionsupporting
confidence: 82%
“…Additionally, the fact that employment status was available only for a subsample should not challenge the results of the study. The effect of employment status on fertility is consistent with that observed in other studies (e.g., Kulu and Washbrook 2014). Does this finding suggest that cultural factors explain the high fertility among women of Pakistani and Bangladeshi descent in the UK?…”
Section: Summary and Discussionsupporting
confidence: 82%
“…This finding has been reported for Armenia and Moldova (Billingsley 2011), Bulgaria (Koycheva 2006, Poland (GaƂęzewska 2012), Romania (Muresan and Hoem 2010), Russia (Rieck 2006), and Ukraine (Perelli-Harris 2008). By contrast, elevated second-birth intensity among highly educated women has been found in the Nordic countries (Hoem and Hoem 1989;OlĂĄh 2003;Vikat 2004;Gerster et al 2007;Kravdal 2007), Belgium (Neels 2006), France (Köppen 2006), and Great Britain (Kreyenfeld and Zabel 2005;Mathews and Sear 2013;Kulu and Washbrook 2014). Likewise, recent analyses on the Czech Republic (Ć t'astnĂĄ 2009), Estonia (Klesment and Puur 2010), and Hungary (Bartus et al 2013) have indicated a positive gradient in second-birth rates for women with advanced education.…”
Section: Theoretical Perspectivesmentioning
confidence: 66%
“…When we studied long-term effects of separation, the variable 'separated' was replaced by time since separation (i.e., 0-4, 5-11, 12-35, 36 months or more). We also included the following variables, which are known to influence the risk of a residential change, in the analyses: age (16-19, 20-24, 25-29, 30-34, 35-39, 40-44, 45-49); current housing tenure (same categories as for destination tenure type); current housing type (detached house, semi-detached house, terraced house, flat, other/missing); educational level (high (university degree or teaching qualification), medium (A Level), low (O Level, CSE, none)); employment status (employed, selfemployed, in education, unemployed, other, missing); and area type of residence (London, large cities with more than 400,000 inhabitants, medium cities with 200,000-400,000 inhabitants, towns with fewer than 200,000 inhabitants but a population density of over 1,000 individuals per km 2 , small towns with fewer than 200,000 inhabitants and a population density of 250-1,000 individuals per km 2 , and rural areas with fewer than 200,000 inhabitants and fewer than 250 individuals per km 2 ) (see Kulu and Washbrook 2014).…”
Section: Variablesmentioning
confidence: 99%